Efficient and Accurate Calibration of Discrete Element Method Parameters for Black Beans - Xuezhen Wang; Qinghang Zhai; Shihao Zhang; Qianwen Li; Hanmi Zhou (Agronomy)
Discrete element parameters of the black bean (BLB) are key to developing high-performance BLB machineries (e.g., seeders and shellers), which are still lacking in previous literature. In this study, the effects of the radius and lifting speed of cylinder-in-cylinder lifting method (CLM) simulations were investigated to efficiently and accurately obtain the repose angle. Discrete element method (DEM) parameters of the BLB were determined by combining the Plackett–Burman Design test, the steepest ascent design test, and the central composite design test. The results show that the measurement moment (i.e., 12 s) of repose angles should be determined when kinetic energy reaches the minimal threshold (1 × 10−6 J) to efficiently and accurately obtain repose angles; too early or too late a measurement can result in inaccurate repose angles or excessive computation time of the computer, respectively. The lifting speed and cylinder radius affected the lateral displacements of BLBs and came at the cost of higher computation time and memory usage. A lifting speed of 0.015 m·s−1 and a radius of 40 mm of the cylinder were determined in CLM simulations. The static friction coefficient and rolling friction coefficient between BLBs significantly affected the repose angles. A static friction coefficient of 0.202 and rolling friction coefficient of 0.0104 between BLBs were obtained based on the optimization results. A low relative error (0.74%) and insignificant difference (p > 0.05) between the simulated and measured repose angles were found. The suggested method can be potentially used to calibrate the DEM parameters of BLBs with good accuracy. The results from this study can provide implications for investigating interactions of BLBs and various BLB processing machines and for the efficient and accurate determination of DEM parameters of crop grains.